RANCANG BANGUN APLIKASI PERENCANAAN PRODUKSI KEBUTUHAN BAHAN BAKU PADA CV. MITRA TECHNO SAINS BERBASIS WEB - Handyono, Kentdra; Eko Wulandari, Sri Hariani; Santoso, Rudi (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2016)
CV. Mitra Techno Sains is a manufacturing company that sells a liquid detergent and softener in Surabaya. The business process begins from customer orders, then production departement will be produce and it will be delivered according to the delivery date has been agreed. Problem that often happen in the company is; (1) process of production and delivery of orders to customers often delayed because they have not good planning and scheduling requirements production material; (2) there is no good information about the raw material needs to be produced; (3) there has been no information on the quantities of raw materials in the warehouse. Those problems can be solved with application design production planning of requirements raw materials that can help in production scheduling and raw material requirements planning. The method can support the planning and scheduling of production and raw materials are Material Requirment Planning (MRP), because MRP suitable to be applied to all manufacturing companies in resolving the issue of raw materials procurement. Based on the results of the implementation and evaluation it can be concluded that the system created can help companies in planning and scheduling of production and raw material requirements.Keywords: Application, Planning, Scheduling, Production, Raw Materials